Aluminium Dapat Dipertukarkan dan Fosfor Tersedia pada Tanah di Provinsi Bangka Belitung: Exchangeable aluminum and available phosphorus in the soils of Bangka Belitung Province - Arief Hartono; Desi Nadalia; Praja Hary Satria (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2022)
Productivity of pepper in Bangka Belitung Province has decreased because one of the causes is the problem of the low nutrient availability. The research was conducted in Bangka Belitung Province to determine the distribution of pH, exchangeable aluminium (Exch Al), and available phosphorus (P) and the correlation among those parameters. Soil samples at depths of 0-30 cm and 30-60 cm were collected at the specified points on a 1: 250,000 scale land system map. The pH was determined by shaking the soil sample with distilled water and the ratio of soil sample and distilled water was 1:5. Exch Al was extracted using 1.00 mol L-1 KCl and determined by titration. Available P was determined using the Bray 1 method. Basic statistic analyses to have minimum, maximum, average and standar deviation (SD) values were conducted. Correlation test among pH, exch Al, and available P to evaluate their relationship were also conducted. The results showed that soils in Bangka Belitung were relatively acid, relatively high exch Al especially in the depth of 0-30 cm and relatively low available P as Bray 1-P. Bray 1-P and exch Al on the depth of 0-30 cm had higher SD than that of the other paramaters. As for correlation analyses, pH significantly negatively correlated with exch Al. pH and exch Al did not correlate with Bray 1-P. This research suggested that soil in Bangka Belitung had problem with soil acidity and low amount of available P in the form of Bray 1-P. The amount of Bray 1-P did not correlate with the amount of exch Al.